Management system and productivity of backyard poultry in Jhenidah district of Bangladesh: a survey - Rahima, Farzana Fiza; Jalil, Md Abdul; Hossain, Md Reshad; Rahman, Md Shaheenur (Asian Journal of Medical and Biological Research, 2023)
This study was carried out to know the current scenarios of rearing backyard poultry in Jhenidah district of Bangladesh. A total of 2832 poultry birds (deshi chicken, sonali, duck and pigeon) were selected from 170 households. The data were collected according to prepared questionnaire. The study revealed that, most of the farmers reared their poultry in semi scavenging system (97.64%). The poultry houses were commonly made of tin and bamboo (88.82%) and some of farmers kept their poultry in houses which were at unsatisfactory level (11.2%). They used polythene, sack, ash, sand, straw, papers separately or together as bedding materials (78.82%) and 21.18% of farmers did not use any bedding materials. They usually cleaned poultry house irregularly (73.53%). The rice (84.71%) as feed supplement followed by boiled rice, paddy, broken rice, wheat and commercial as well, was commonly given twice (62.9%) in a day. The farmers did not usually use feeder and waterer (44.12%) and use only 8.82% of vaccine. The supplementary feed to each deshi chicken, sonali, duck and pigeon per day were 32.77 g, 38.70 g, 82.04 g and 12.40 g gaining average body weight of 1.19 kg, 1.36 kg, 1.22 kg and 315.35 g respectively. The average egg production per deshi chicken, sonali, duck and pigeon per year were 37.27, 47.30, 84.66, and 19.90 containing average weight 35.01 g, 41.20 g, 52.68 g and 11.10 g successively. Furthermore, the mean hatchability was found 77.50% in deshi chicken, 79.25% in sonali, 78.95% in duck and 97.45% in pigeon along with 28.79% significant (P<0.05) mortality in deshi chicken, 30.35% in sonali, 14.50% in duck and 11.40% in pigeon consecutively. The prevalence of diseases were investigated as Newcastle disease, fowl cholera, duck cholera, duck plague and pigeon pox. Diseases (54.1%) are the most current constraints followed by lack of knowledge, predators for poultry rearing in backyard system. This study will support farmers by enhancing their income through improved management practice in backyard poultry. Asian J. Med. Biol. Res. 2023, 9 (1), 1-8